Policy mix for environmental protection: A transaction cost approach - Beat Bürgenmeier (Fondazione Eni Enrico Mattei (FEEM), 1999)
This paper uses a transaction cost approach in order to classify the different policy options that are currently discussed in relation to the Kyoto protocol. It analyses the market as only one of the possible collective decision making processes, which are available to operationalize the concept of sustainable development. The firm, the third sector, the government, the market are analysed as collective decision making processes. They are socially constructed in the sense that they are institutions, which are subject to change. Compared to initial and already existing institutions, the policy options for environmental protection are evaluated in the light of the associated transaction costs. The paper concludes with the recommendation for new institutional arrangements minimising transaction costs at both the national and international level.
Keywords: D23; Q20; Q28; Q38; 330; Kyoto protocol; Policy mix; Transaction costs organisations and contacts; National guidelines; International institutions; Internationale Umweltpolitik; Umweltpolitik; Policy-Mix; Transaktionskosten; Internationale Wirtschaftsorganisation; Theorie